(untitled) (Cadernos de Sociomuseologia, 2014)
The article deals with the emergence in Brazil of a new type of museum: the Museum of the Landless Rural Workers Movement (MST). We discuss this sense as well as the social and political need and eplain that this type of museums may have a major significance for the country. We show that this new design museum, also emerged from the new museology. Keywords: MST Museum; memory of struggle; museology; agrarian reform; social development.